Estudos de dispersão de lagartas em milho e soja visando ao manejo de pragas no Brasil e EUA - Pannuti, Luiz Eduardo da Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Corn (Zea mays L.) is one of the most cultivated crops worldwide. However, its productivity is constantly threatened by several factors such as the attack of insect pests. Among them stand out the species from Noctuidae family, including the fall armyworm Spodoptera frugiperda(J.E. Smith) (Lepidoptera: Noctuidae), the western bean cutworm Striacosta albicosta(Smith) (Lepidoptera: Noctuidae), and the old world cotton bollworm Helicoverpa armigera(Hubner) (Lepidoptera: Noctuidae). Alterations in crop systems such as off-season plantations and succession of host crops, combined with the extensive use of transgenic Bt corn, have been demanding more information related to various behavioral aspects of these insects, which can directly influence important components in the implementation of integrated pest management (IPM) and resistance management (IRM) of these pests. Some of these behavioral aspectsare not easy to observe in field conditions, and require the use of marking techniques for individuals. In this sense, this work aimed to evaluate the larval movement of noctuidae species in reproductive corn stages, as well as develop marking techniques for early instars and test their application in behavioral studies of these insects. Initially, the on-plant larval movement of the fall armyworm was investigated in field (US and Brazil), and greenhouse conditions (Brazil), as well as the feeding behavior of the larvae on different corn tissues in laboratory. In another study, the dispersion of the western bean cutworm and fall armyworm larvae was characterized in corn fields (USA). In the last step, new marking techniques of early larval instars were investigated forH. armigera, and their application were tested in a behavioral study at ...

O milho (Zea mays L.) é uma das culturas mais cultivadas em todo o mundo. No entanto, sua produtividade está constantemente ameaçada por diversos fatores como o ataque de insetos-praga. Entre eles, se destacam os insetos da família Noctuidae, como Spodoptera frugiperda(J.E. Smith) (Lepidoptera: Noctuidae), Striacosta albicosta(Smith) (Lepidoptera: Noctuidae) e Helicoverpa armigera(Hubner) (Lepidoptera: Noctuidae). Alterações no sistema de cultivo como plantios safrinha e sucessão de culturas hospedeiras, aliadas à ampla utilização de milho transgênico Bt vêm demandando maior informações relacionadas a diversos aspectos comportamentais desses insetos, os quais podem influenciar diretamente importantes componentes na implementação de um manejo integrado (MIP) e manejo de resistência (MRI) dessas pragas. Alguns desses estudosnão são facilmente estudadosem condições de campo,assim, exigindo a utilização de técnicas de marcação de indivíduos. Nesse sentido, o trabalho teve como objetivo avaliar o movimento larval de espécies de noctuídeos na planta e entre plantas de milho, bem como desenvolver técnicas de marcação de lagartas de ínstares iniciais para sua aplicação em estudos comportamentais desses insetos. Inicialmente, foi investigado o movimento larval de S. frugiperda na planta de milho em condições de campo (EUA e Brasil) e casa de vegetação (Brasil), bem como o comportamento alimentar da lagarta em estágios reprodutivos de milho em laboratório. Em outro estudo, foi caracterizada a dispersão de lagartas de S. albicosta e S. frugiperda em campos de milho (EUA). Por fim, foram investigadas novas técnicas de marcação de lagartas de ínstares iniciais de H. armigera e ...
Studies of larval dispersion in corn and soybean aiming pest management in Brazil and the U.S
Keywords: Milho - Doenças e pragas; Soja - Doenças e pragas; Lagarta; Pragas agricolas - Controle integrado; Relação inseto-planta; Agricultural pests